2020
DOI: 10.3389/fcimb.2020.594856
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Characterisation of Campylobacter jejuni Isolates From a Waterborne Outbreak

Abstract: Campylobacter infections are the leading cause of bacterial gastroenteritis. In Europe, over 246,000 cases are confirmed annually. Infections are often transmitted via contaminated food, such as poultry products, but water may be the source of infection as well. The aim of this study was to characterise a selection of Campylobacter jejuni human isolates, together with a water isolate, from a waterborne outbreak in Norway in 2019, including human isolates from early, mid-, and late epidemic. The isolates were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Although wells infected with HC isolates produced the lowest amount of IL-8 in the present study, the difference was not statistically different from CC, LC, UC, CD and D isolates. Furthermore, C. jejuni produced higher levels of IL-8 than all C. concisus isolates; a control isolate chosen due to its well-known pathogenic effects in in vitro settings [ 20 , 21 ]. Nevertheless, despite that C. concisus may be considered a commensal based on these observations, the bacterium still stimulates the innate immune system in a non-specific way and thereby hypothetically plays a part in mucosal inflammation if abundant in the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Although wells infected with HC isolates produced the lowest amount of IL-8 in the present study, the difference was not statistically different from CC, LC, UC, CD and D isolates. Furthermore, C. jejuni produced higher levels of IL-8 than all C. concisus isolates; a control isolate chosen due to its well-known pathogenic effects in in vitro settings [ 20 , 21 ]. Nevertheless, despite that C. concisus may be considered a commensal based on these observations, the bacterium still stimulates the innate immune system in a non-specific way and thereby hypothetically plays a part in mucosal inflammation if abundant in the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Because campylobacteriosis is often associated with contaminated food products and exposure to animals, whole-genome sequencing (WGS) might become the preferred typing method, and analysis of isolates from various sources should be a major component of studying disease ecology and epidemiology ( Park et al, 2020 ). At present, WGS has been considered the most informative and discriminative typing method to examine the genomic characteristics of Campylobacter isolates with high resolution ( Davies et al, 2020 ), allowing for comprehensive phylogenetic analyses of numerous traits associated with virulence or antibiotic resistance ( Fiedoruk et al, 2019 ). Our previous epidemiological research revealed that the GBS maker serotype HS19 was significantly more prevalent in isolates from cattle than other animal populations circulating in China.…”
Section: Introductionmentioning
confidence: 99%
“…Their helical shape and long polar flagella allow them to move quickly and survive within the mucosal layer of the gastrointestinal tract [1]. Campylobacter infection usually begins in the jejunum and ileum and progresses distally to affect the cecum and colon [2].…”
Section: Discussionmentioning
confidence: 99%
“…The route of infection is often unknown, but it can be caused by oral ingestion of raw or undercooked meat or food secondarily contaminated with raw meat [ 1 ]. After an incubation period of approximately three days, infections are established mainly in the colon and rectum [ 2 ]. The disease is found worldwide, regardless of the climate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation